2011
DOI: 10.1371/journal.pone.0018413
|View full text |Cite
|
Sign up to set email alerts
|

Co-Crystal Structures of PKG Iβ (92–227) with cGMP and cAMP Reveal the Molecular Details of Cyclic-Nucleotide Binding

Abstract: BackgroundCyclic GMP-dependent protein kinases (PKGs) are central mediators of the NO-cGMP signaling pathway and phosphorylate downstream substrates that are crucial for regulating smooth muscle tone, platelet activation, nociception and memory formation. As one of the main receptors for cGMP, PKGs mediate most of the effects of cGMP elevating drugs, such as nitric oxide-releasing agents and phosphodiesterase inhibitors which are used for the treatment of angina pectoris and erectile dysfunction, respectively.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(95 citation statements)
references
References 38 publications
6
89
0
Order By: Relevance
“…Such partial agonism of cAMP is not fully explained by previously solved structures of PKG I␤, as they reveal very similar structural rearrangements of both CNB domains in response to either cAMP or cGMP binding (Fig. 1, b-d) (2,17,18) that are analogous to structural rearrangements observed for other CNB domains (8, 12, 24 -29). Hence, we hypothesize that the partial agonist response of PKG I␤ to cAMP may reflect differences in the dynamics of cAMP versus cGMP-bound PKG I␤.…”
mentioning
confidence: 73%
See 1 more Smart Citation
“…Such partial agonism of cAMP is not fully explained by previously solved structures of PKG I␤, as they reveal very similar structural rearrangements of both CNB domains in response to either cAMP or cGMP binding (Fig. 1, b-d) (2,17,18) that are analogous to structural rearrangements observed for other CNB domains (8, 12, 24 -29). Hence, we hypothesize that the partial agonist response of PKG I␤ to cAMP may reflect differences in the dynamics of cAMP versus cGMP-bound PKG I␤.…”
mentioning
confidence: 73%
“…By binding to PKG, cGMP regulates intracellular signaling pathways that control a wide range of intracellular processes, such as cell differentiation, platelet activation, memory formation, and vasodilation (1)(2)(3)(4)(5). The PKG signaling pathways are often distinct from those regulated by cAMP-dependent proteins such as protein kinase A (PKA) (6 -12).…”
mentioning
confidence: 99%
“…The cAMP-bound structure of the HCN carboxyl-terminal region has been solved for several HCN channels (10)(11)(12)(13)(14) and is similar to the agonist-bound structures of many other CNBDcontaining proteins (15)(16)(17)(18)(19). However, the agonist-free structure of this protein is still controversial.…”
Section: Discussionmentioning
confidence: 93%
“…Each of the subunits contains two domains: the cyclic nucleotide-binding domain (CNBD) and the C-linker domain. The CNBD exhibits strong structural similarity to the CNBDs of other cyclic nucleotide-binding proteins, including cAMP-dependent protein kinase (PKA), the guanine nucleotide exchange factor Epac, and the Escherichia coli catabolite gene activator protein (CAP) (15)(16)(17)(18)(19). The CNBD consists of an eight-stranded antiparallel β-roll, followed by two α-helices (B-helix and C-helix).…”
mentioning
confidence: 99%
“…ϭ 0.5 Å), with the exception of partial uncoiling of the FЈ-helix and of the C-terminal half of the C-helix, which was unresolved (25). However, it has been suggested that the similarity between the apo-and holo-HCN2 IR tetramer structures might at least in part be due to crystal packing and a co-crystallized bromide ion mimicking the cAMP phosphate (25), as also observed for other apo-CBDs (26,27). Furthermore, size exclusion chromatography and analytical ultracentrifugation indicate that in solution the IR of HCN2 and HCN4 is primarily monomeric in the apo-form, with minimal or no tetrameric IR detected (11,21).…”
mentioning
confidence: 93%